Selected Issues in Strategic Planning of Public Sector in Indonesia - Fajar Eko Antono; Keziah Cahya Virdayanti (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
Development planning is one of the important functions of government in the implementation of the state administration. Progress of a country depends on the quality of its development planning implemented by government agencies (public sector), which will determine the success of achieving national development goals. The problems of development planning are inherently in the development planning system itself. There are still some weaknesses in strategic planning in the public sector such as: planning as a legal-formal process; errors in goal setting; difficulty in predicting the future; less strategic participatory planning processes; difficulties in formulating systematic, tiered performance indicators; difficulties in measuring the impact and benefit performance; and difficulties in prioritization in programming and budgeting. There are short-term problems that are difficult to overcome, but for some other problems can be made to overcome them by adding refinements to existing mechanisms as well as adding new mechanisms in strategic planning practice.